1 "y = e^{mx}" is solution of "\\frac{dy}{dx} = 3y"
So differentiate y with respect to x,
"\\frac{dy}{dx} = me^{mx}"
now, as per equation, "(m+3)e^{mx} = 0"
solution for this is "m=-3" only.
2 Given differential equation,
"\\frac{dy}{dx} = \\sqrt {y^2 - 25}"
Solving this equation,
"\\int \\frac{dy}{\\sqrt {y^2-25}} = \\int dx"
"ln|y+\\sqrt {y^2-25}| = x + lnC" . . . . . . . . (i)
At point (1,7), value of constant C,
"ln|7+\\sqrt{49-25}| = 1 + lnC"
"lnC = ln|7+\\sqrt{24}| -1"
putting back value in equation (i)
"ln|y+\\sqrt{y^2 - 25}| = x + ln|7+\\sqrt{24}|-1"
This equation is unique solution for differential equation.
Comments
Leave a comment